Psychological Incentives, Financial Incentives, and Risk Attitudes in Tournaments: An Artefactual Field Experiment - Bram Cadsby; Jim Engle-Warnick; Tony Fang; Fei Song (Institute for the Study of Labor (IZA), 2015)
Tournaments are widely used to assign bonuses and determine promotions because of the link between relative performance and rewards. However, performing relatively well (poorly) may also yield psychological benefits (pain). This may also stimulate effort. Through a real-effort artefactual field experiment with factory workers and university students as a comparison group in China, we examine how both psychological and financial incentives, together with attitudes toward risk, may influence motivation and performance. We provided performance-ranking information both privately and publicly, with and without rank-based financial incentives. Our results show that performance-ranking information had a significant motivational effect on average performance for students, but not for that of workers. Adding financial incentives based on rank provided little evidence of further improvement. Much of the difference between workers and students can be explained by differences in attitudes toward risk. Indeed, for both groups financial and psychological incentive effects are both inversely related to individual levels of risk aversion, and are positive and significant both for workers and for students who are sufficiently risk-tolerant.
Keywords: J30; J24; J33; C93; C91; 330; tournament; peer pressure; performance feedback; social comparison; incentives; risk aversion; artefactual field experiment